2017
DOI: 10.1038/cddiscovery.2017.74
|View full text |Cite
|
Sign up to set email alerts
|

Orai1, 2, 3 and STIM1 promote store-operated calcium entry in pulmonary arterial smooth muscle cells

Abstract: Previous studies have demonstrated that besides the classic canonical transient receptor potential channel family, Orai family and stromal interaction molecule 1 (STIM1) might also be involved in the regulation of store-operated calcium channels (SOCCs). An increase in cytosolic free Ca2+ concentration promoted by store-operated Ca2+ entry (SOCE) in pulmonary arterial smooth muscle cells (PASMCs) is a major trigger for pulmonary vasoconstriction and proliferation and migration of PASMCs. In this study, our dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 54 publications
2
62
0
Order By: Relevance
“…Increasing evidence has suggested the important roles of Orai and TRPC channels in PAH. Orai1, Orai12, and Orai3 can promote SOCE in PASMCs and may serve as potential therapeutic targets for chronic hypoxia-induced pulmonary hypertension [ 36 ]. Dragoni et al suggested that Orai3 is overexpressed in primary myelofibrosis-endothelial colony forming cells (ECFCs) that are EPC subset and thus resulted in the upregulation of SOCE [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has suggested the important roles of Orai and TRPC channels in PAH. Orai1, Orai12, and Orai3 can promote SOCE in PASMCs and may serve as potential therapeutic targets for chronic hypoxia-induced pulmonary hypertension [ 36 ]. Dragoni et al suggested that Orai3 is overexpressed in primary myelofibrosis-endothelial colony forming cells (ECFCs) that are EPC subset and thus resulted in the upregulation of SOCE [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The function of the STIM2.3 variant still remains unclear [46,47]. Orai2 and Orai3 proteins have also been shown to drive I CRAC currents after depletion of the intracellular stores [48][49][50] and their regulation and physiological role are less known as compared to Orai1. Therefore, it is currently widely established that the Orai-STIM complex, mainly Orai1-STIM1, constitutes the highly selective CRAC channel.…”
Section: Trpc Channels In the Stim1-orai1 Scenariomentioning
confidence: 99%
“…Most recent studies have shown that aberrant activation of STIM1‐Orai1 impairs the control of cellular Ca 2+ levels that cause vascular dysfunction associated with arterial hypertension . In a model of chronic hypoxia induced pulmonary hypertension, the expression of Orai1 and Orai2 were seen to be upregulated in pulmonary arteries and pulmonary arterial smooth muscle cells after chronic hypoxia exposure . Increased expression of STIM1 and Orai1 proteins have also been implicated in vascular smooth muscle cell remodeling following balloon injury in the rat carotid artery .…”
Section: Discussionmentioning
confidence: 99%
“…25 In a model of chronic hypoxia induced pulmonary hypertension, the expression of Orai1 and Orai2 were seen to be upregulated in pulmonary arteries and pulmonary arterial smooth muscle cells after chronic hypoxia exposure. 26 Increased expression of STIM1 and Orai1 proteins have also been implicated in vascular smooth muscle cell remodeling following balloon injury in the rat carotid artery. 27 Furthermore, this study also shows that upregulation of STIM1 and Orai1 is required for nuclear translocation and activation of the transcription factor nuclear factor for activated T cell (NFAT) to allow proliferation of the vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%